The Role of Sunspots Magnetic Configuration in the Formation of Umbral Fine-Structures - Hashem Hamedivafa (Iranian Journal of Astronomy and Astrophysics)
We use spectro-polarimetric data recorded by Hinode to analyze the magnetic field configuration of a part of a sunspot (AR10923) where a bundle of penumbral filaments are intruding into its umbra. We want to explore the role of the sunspot magnetic configuration in the formation and kinematics of the fine-structures, such as umbral dots and light bridges, inside the sunspot umbra. Both direct inferences from polarization Stokes profiles and the inversion results using the SIR code imply a well-arranged magnetic field configuration in the umbra where moving umbral dots are easily formed at the leading edges of the rapidly intruding penumbral filaments. We suggest that the magnetic field topology is rearranged via magnetic reconnection process by which a part of the magnetic energy is converted into thermal and kinetic energy, leading to the orderly aligned magnetic field lines. This new configuration causes the umbral fine-structures to form easily and more frequent.